Human Language Technology. Challenges for Computer Science and Linguistics 4th Language and Technology Conference, LTC 2009, Poznan, Poland, November 6-8, 2009, Revised Selected Papers - Vetulani, Zygmunt; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 4th Language and Technology Conference: Challenges for Computer Science and Linguistics, LTC 2009, held in Poznan, Poland, in November 2009. The 52 revised and in many cases substantially extended papers presented in this volume were carefully reviewed and selected from 103 submissions. The contributions are organized in topical sections on speech processing, computational morphology/lexicography, parsing, computational semantics, dialogue modeling and processing, digital language resources, WordNet, document processing, information processing, and machine translation.
Keywords: Computer science; Artificial intelligence; Text processing (Computer science; Translators (Computer programs).; Optical pattern recognition; Biometrics; Information systems; Computer Science; Language Translation and Linguistics; Document Preparation and Text Processing; Computer Appl. in Arts and Humanities; Biometrics; Pattern Recognition; Artificial Intelligence (incl. Robotics).